Community Service for Legal and Legal Awareness Prevention of Violence Against Children in Bone District - Damayanti, Rika; Suriyati, Suriyati; Sandra, Gustika; Rasyid, Mukhawas; Bakri, Muh. (Journal of Universal Community Empowerment Provision, 2024)
The government stipulates Law Number 35 of 2014, which amends Law Number 23 of 2002 concerning Child Protection. This legislation explicitly delineates that children represent the successors of the nation's generation and must be afforded protection from all forms of violence and discrimination. The established regulations serve as an appropriate legal foundation for the provision of protection for children. This counseling activity is conducted to educate the community as a proactive measure to prevent and address crimes or criminal acts. The proliferation of counseling initiatives undertaken by law enforcement agencies and local governmental bodies is anticipated to enhance public comprehension regarding the importance of preventive measures against criminal activities, particularly those involving violence directed at children. This activity is conducted in three stages, specifically: Focus Group Discussion (FGD), the dissemination of child violence law policies, and the establishment of a collective commitment to encourage the community to adhere to the law. The findings of the community service indicated that insufficient parental supervision and a lack of awareness among children regarding problem-solving through deliberation have contributed to the emergence of numerous groups of children. In the interim, initiatives undertaken in partnership with law enforcement to address crimes against children in Bone Regency encompass: guidance, peace efforts, counseling, and patrols. Educating families regarding the significance of supervising their children is essential to prevent their offspring from becoming either victims or perpetrators of criminal activities. Delivering continuous legal education in light of the significant role that society plays in the prevention of crime, particularly violent offenses against children.